Cross reactivity of serological response to SARS-CoV-2 vaccination with viral variants of concern detected by lateral flow immunoassays. Issue 4 (October 2021) - Ebanks, Daniel; Faustini, Sian; Shields, Adrian; Parry, Helen; Moss, Paul; Plant, Tim; Richter, Alex; Drayson, Mark
Highlights: IgG anti-SARS-CoV-2 spike glycoprotein antibody levels were greatest after vaccination and lowest after natural non-hospitalised infection. Using lateral flow tests incorporating wildtype (Wuhan) spike glycoprotein, 40 serum samples post second vaccine dose were positive. Changing the spike glycoprotein in the lateral flow tests to that from Alpha or Beta or Gamma variants of concern resulted for all three variants, in 40/40 positive results albeit at lower levels. Changing the spike glycoprotein in the lateral flow tests to that from the Delta variant of concern (VOC) resulted in 37/40 positive results. The WHO standard NIBSC 20/136 had reactivity to Alpha, Beta and Gamma VOC down to 7 IU/ml and for the Delta VOC to 15 IU/ml.